Exploring foreign language teaching: Experiences and reflections from the practicum (2023)
The Practicum is a practical experience that is an essential requirement to forge our formation as future university professionals in the field of teaching. Over the course of eight months, students are immersed in the reality of being foreign language teachers, having the opportunity to assume crucial responsibilities such as lesson planning and the creation of teaching materials. This exercise not only provides them with a space to apply the knowledge acquired in their theoretical training, but also allows them to improve practical pedagogical skills. During this process, students have the flexibility to choose the educational organization of their choice. This practicum took place in the educational institution Madre Laura, located in the city of Cartagena in Piedra Bolívar neighborhood near to the University of Cartagena. This organization is legally recognized by the Secretariat of District Education of Cartagena de Indias, by Resolution No. 0176 of April 18, 2012, to teach Formal Education in the locations Madre Laura, José María del Castillo y Rada Andalucía, at the levels of Preschool, Basic Primary and Basic Secondary.